Effective Personnel Recruitment Management Strategies For The Bengkulu Regional Police - Lastomo Lastomo; Ahmad Soleh; Muhammad Rahman Febliansa (UNIVED Press, 2026)
The objectives of this study are: 1) to describe and analyze effective recruitment management strategies to produce quality police personnel; 2) to describe and analyze the factors that influence the effectiveness of recruitment management for the Bengkulu Regional Police personnel; and 3) to describe and analyze solutions for overcoming the factors that affect the effectiveness of recruitment management for personnels of the Bengkulu Regional Police.This research is qualitative with a descriptive approach. Data collection techniques used observation, interviews, and documentation. The data analysis technique in this study used data triangulation based on Miles and Huberman's theory, namely data reduction, data display, and verification/conclusion. The results of this study indicate: the recruitment management strategy for the Bengkulu Regional Police personnel has been directed toward the principles of professionalism, transparency, accountability, and responsiveness to the local context. The planning stage becomes an important foundation because it determines the alignment between personnel needs and the dynamics of community security and social conditions. Recruitment implementation, marked by the application of digitization, the BETAH principles, and involvement of external stakeholders, demonstrates the seriousness of the National Police in building a selection process that is accountable and open. Meanwhile, the evaluation carried out comprehensively, participatively, and oriented toward continuous improvement makes the recruitment process not only function as a technical selection mechanism but also as an organizational learning tool. The factors supporting the success of the recruitment strategy include national regulations, leadership support, interagency synergy, availability of adequate resources, community involvement, and the quality of the recruitment team and internal supervisors. However, there are still obstacles such as negative public perceptions of the police profession, limited digital literacy among prospective candidates, technical barriers in implementing computer-based systems, and limited access to information in rural areas. Efforts by the Bengkulu Regional Police to overcome these obstacles are visible through improved public communication quality, provision of adaptive technological solutions, and intensive internal coordination.